1978
DOI: 10.1001/jama.1978.03280500056020
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Against Megakaryocytes in Idiopathic Thrombocytopenic Purpura

Abstract: (30-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
7

Year Published

1988
1988
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 0 publications
0
36
0
7
Order By: Relevance
“…During maturation, MK express CD41/CD61 and CD42b/CD42a on their surfaces, 6,7,26 so it is likely that the binding of antiplatelet autoantibodies could inhibit MK maturation [27][28][29] and interfere with platelet release. During endomitosis, the ploidy of diploid (2N) MK precursors increases 30 and each of these mature MK is able to release thousands of platelets 31 by extending proplatelets.…”
Section: Discussionmentioning
confidence: 99%
“…During maturation, MK express CD41/CD61 and CD42b/CD42a on their surfaces, 6,7,26 so it is likely that the binding of antiplatelet autoantibodies could inhibit MK maturation [27][28][29] and interfere with platelet release. During endomitosis, the ploidy of diploid (2N) MK precursors increases 30 and each of these mature MK is able to release thousands of platelets 31 by extending proplatelets.…”
Section: Discussionmentioning
confidence: 99%
“…15 It is not surprising that ITP autoantibody might affect platelet production because it has been well shown that the common ITP autoantigens, GPIIb-IIIa and GPIb-IX, are expressed on the surfaces of megakaryocytes 7 and that ITP autoantibody binds to megakaryocytes. 16,17 Attempts to use megakaryocyte colony formation to study thrombopoiesis in ITP have given contradictory results. Some groups, culturing ITP bone marrow, have found increased numbers of megakaryocyte colony-forming units (CFU-Ms), 18,19 whereas others have found decreased numbers of CFU-Ms. 20 Similarly, one group 21 reported that ITP plasma did not affect CFU-M formation by normal cells, yet another group 18 noted increased CFU-M formation in the presence of ITP serum.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some studies revealed autoantibodies binding to either platelets intramedullary or megakaryocytes [29], thus affecting thrombopoiesis [30,31].…”
Section: Discussionmentioning
confidence: 99%